The Origin of Protoconversation: An Examination of Caregiver Responses to Cry and Speech-Like Vocalizations - Yoo, Hyunjoo; Bowman, Dale A.; Oller, D. Kimbrough (Frontiers in Psychology, 2018)
Turn-taking is a universal and fundamental feature of human vocal communication. Through protoconversation, caregivers play a key role for infants in helping them learn the turn-taking system. Infants produce both speech-like vocalizations (i.e., protophones) and cries from birth. Prior research has shown that caregivers take turns with infant protophones. However, no prior research has investigated the timing of caregiver responses to cries. Such research could be important in evaluating developing emotional bonds. The present work is the first to systematically investigate different temporal patterns of caregiver responses to protophones and to cries. Results showed that, even in infants’ first three months of life, caregivers were more likely to take turns with protophones and to overlap with cries. The present study provides evidence that caregivers are intuitively aware that protophones and cries are functionally different: protophones are treated as precursors to speech, whereas cries are treated as expressions of distress.